Morphoanatomy and ultrastructure studies on embryogenic and non-embryogenic calluses of Williams banana (Musa sp.): I. Inmature male flowers. - Ramírez Villalobos, M.; de García, E.; Lindorf, H.; Finol, H. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2013)
The bananas belonging to the Cavendish subgroup are the most cultivated worldwide, but they have low fertility, slow propagation and long time span from one generation to the next. Application of in vitro somatic embryogenesis (SE) has greatly increased Musa germplasm handling for the purposes of clonal propagation and improvement of banana cultivars. In the present investigation, the morphoanatomy and ultrastructure of embryogenic and non-embryogenic calluses (EC and NC, respectively) obtained from immature male flowers of WilliamsÂ´s banana plants were examined by means of light microscopy, and by transmission and scanning electron microscopy. Immature male flowers were cultured in callus-induction medium; samples of both kinds of callus were taken at various intervals and processed for later observation. The NC formation from the male flowers was observed after two months of culture, two types of structure were observed; a lax one, showing large elongated hyaline cells, and a watery one with round cells. The NCs presented variability of cell shape, poor and unequal cytoplasmic content, senescent appearance, and intercellular spaces with accumulation of unidentified materials. Primary somatic embryos (which represent an early morphological marker of SE) were detected after four months in the flowers, then, they developed to ECs at next two months. The creamy white ECs with a granular structure showed clearly a cellular organization split into three regions, each with its own distinctive features. The ultrastructural study revealed that the EC cells contained moderate numbers of mitochondria and plastids, and very few drops of lipids. These observations add further important information to the structural studies of SE in bananas, which would help in the understanding of the SE process.